Calcium antagonists in patients with high cardiovascular risk - A. A. Garganeeva (Кардиоваскулярная терапия и профилактика)
The choice of optimal antihypertensive medications in patients with arterial hypertension (AH) and high cardiovascular risk remains one of the important problems in modern cardiology. Calcium antagonists (CA) have demonstrated their effectiveness in various clinical situations, according to numerous randomised clinical trials. However, despite their high effectiveness and safety, CA are still used relatively rarely in the real-world Russian clinical practice.